Analisis Reflektif Tentang Presentasi Dan Diskusi Mahasiswa Pada Mata Kuliah Karya Tulis Ilmiah (KTI) Melalui Fitur Grup Whatsapp (WA) Di Masa Pandemi Covid-19 - Fedik Novibriawan; Sa'dun Akbar (Pendagogia: Jurnal Pendidikan Dasar, 2021)
The purpose of this study is to (1) describe the implementation of lectures and the ease of use of the WhatsApp (WA) group feature as a medium for presentation and discussion among students, (2) and researchers want to know the level of effectiveness of presentations and discussions through the WhatsApp (WA) group feature. done by students. This study uses a qualitative descriptive design approach. The researcher gave a questionnaire to 37 students as respondents, the purpose of the questionnaire was to find information about student responses to the experience of the presentation and discussion process using the WhatsApp (WA) group feature. The results showed that the use of the WhatsApp (WA) group feature as a medium for presentations and discussions among students was considered effective (assignments, discussion processes and mid-semester exam scores) and easy to do. This can provide convenience and increase student activity in the presentation and discussion process. The way that can be done when the presentation process takes place is through the WhatsApp (WA) group feature, namely by including a link to the presentation video that has been made previously, then the discussion process can be carried out by typing responses in the comments column and can be done by recording a voice known as the voice note on the WhatsApp (WA) group feature.The purpose of this study is to (1) describe the implementation of lectures and the ease of use of the WhatsApp (WA) group feature as a medium for presentation and discussion among students, (2) and researchers want to know the level of effectiveness of presentations and discussions through the WhatsApp (WA) group feature. done by students. This study uses a qualitative descriptive design approach. The researcher gave a questionnaire to 37 students as respondents, the purpose of the questionnaire was to find information about student responses to the experience of the presentation and discussion process using the WhatsApp (WA) group feature. The results showed that the use of the WhatsApp (WA) group feature as a medium for presentations and discussions among students was considered effective (assignments, discussion processes and mid-semester exam scores) and easy to do. This can provide convenience and increase student activity in the presentation and discussion process. The way that can be done when the presentation process takes place is through the WhatsApp (WA) group feature, namely by including a link to the presentation video that has been made previously, then the discussion process can be carried out by typing responses in the comments column and can be done by recording a voice known as the voice note on the WhatsApp (WA) group feature.